Paraplatyptilia terminalis ... - Ustjuzhanina, Anna (Zenodo, 2017)
ParaPlatyPtilia terminalis (Erschoff, 1877) Material examined. 1 ♂, 1 ♀ (CUK), Mongun-Taiga, 24.vi.1968; 2 ♂ (ZISP), Tes-Chem, 26.vi.1969, Yu. Kostyuk; 1 ♂ (CUK), Shuurmak vill., 17.vi.2001, P. Ustjuzhanin; 1 ♂ (CUK), Sush', 17.vi.2002, R. Yakovlev. Distribution. Siberia, NE China, Russian Far East (Kamchatka). ... : Published as part of Ustjuzhanina, Anna, 2017, Pterophoridae (Lepidoptera) fauna of the Republic of Tuva, pp. 317-328 in Zootaxa 4319 (2) on page 321, DOI: 10.11646/zootaxa.4319.2.3, http://zenodo.org/record/889135 ...